Polar mesosphere summer echo strength in relation to solar variability and geomagnetic activity during 1997–2009 - M. Smirnova; E. Belova; S. Kirkwood (Annales Geophysicae, 2011)
This paper is based on measurements of Polar Mesosphere Summer Echoes (PMSE) with the 52 MHz radar ESRAD, located near Kiruna, in Northern Sweden, during the summers of 1997–2009. Here, a new independent calibration method allowing estimation of possible changes in antenna feed losses and transmitter output is described and implemented for accurate calculation of year-to-year variations of PMSE strength (expressed in absolute units – radar volume reflectivity η). The method is based on radar-radiosonde comparisons in the upper troposphere/lower stratosphere region simultaneously with PMSE observations. Inter-annual variations of PMSE volume reflectivity are found to be strongly positively correlated with the local geomagnetic K-index, both when averaged over all times of the day, and when considering 3-h UT intervals separately. Increased electron density due to energetic particle precipitation from the magnetosphere is suggested as one of the possible reasons for such a correlation. Enhanced ionospheric electric field may be another reason but this requires further study. Multi-regression analysis of inter-annual variations of PMSE η shows also an anti-correlation with solar 10.7 cm flux and the absence of any statistically significant trend in PMSE strength over the interval considered (13-years). Variations related to solar flux and K-index account for 86% of the year-to-year variations in radar volume reflectivity.